Exercise-Induced Myokines With Therapeutic Potential for Muscle Wasting - Piccirillo, Rosanna (Frontiers in Physiology, 2019)
Skeletal muscle is a highly vascularized tissue able to secrete proteins that have been given the name of myokines. These muscle-secreted factors are endowed with biological functions on muscle itself (autocrine effect) or on short- or long-distant organs (paracrine/endocrine effects) and control processes such as metabolism, angiogenesis or inflammation. Very diverse diseases ranging from genetic myopathies to cancers are emerging to cause dysregulated secretion of myokines from skeletal muscles. Myokines are involved also in the control of muscle size and are important to be restored to normal levels to alleviate muscle wasting, occuring during various conditions, like cancer, untreated diabetes, chronic obstructive pulmonary disease (i.e. COPD), aging or heart failure. Interestingly, many myokines are induced by exercise (i.e. muscle-derived exerkines) and some even by specific subtypes of physical activity, but more studies are needed in this direction. Most of exercise-induced myokines travel throughout the body by means of extracellular vesicles. Restoring myokines by physical activity may be added to the list of mechanisms by which exercise exerts preventative or curative effects against a vast number of diseases, including the deleterious muscle wasting associated with them. In the future, expanding our understanding about which myokine could be beneficial to restore in specific diseases may help to prescribe more tailored exercise or myokine-based drugs.